Species delimitation of some argyreia (Convolvulaceae) using phenetic analyses: Insights from leaf anatomical data reveal a new species - Natthaphong Chitchak (2019)
© 2018, Canadian Science Publishing. All rights reserved. Argyreia Lour. is one of the most taxonomically complex genera of the morning glory family (Convolvulaceae). The number of named species is now 135, and new species are regularly being described. There are several species complexes that are morphologically similar and difficult to tell apart. Therefore, the aim of this study is to explore the species identification criteria for Argyreia, especially new sources for taxonomically informative characters. Ten accessions representing three morphologically similar Argyreia operational taxonomic units (OTUs) were collected and their anatomical characters were investigated using the leaf peeling technique and paraffin sectioning method. Anatomical character states were analyzed using two phenetic analysis methods: clustering analysis (CA) and principal component analysis (PCA). Three distinct clusters were clearly separated in both PCA and CA at the internal similarity coefficient of 0.48 with a high R-value of 0.89757. Nineteen effectively distinguishable character states were derived from the high loadings of the first two components. In conclusion, two of the separated groups were matched with known species, and the third separated group is here delineated as a new species. Therefore, a new species, Argyreia gyrobracteata Traiperm & Chitchak, is described and illustrated together with ecological data and a preliminary conservation assessment.